Bovine colostrum supplementation as a new perspective in depression and substance use disorder treatment: a randomized placebo-controlled study - Durkalec-Michalski, Krzysztof; Główka, Natalia; Podgórski, Tomasz; Odrobny, Weronika; Krawczyński, Marcin; Botwina, Ryszard; Bodzicz, Stanisław; Nowaczyk, Paulina M. (Frontiers in Psychiatry, 2024)
Introduction This randomized, placebo-controlled, double-blind, parallel study aimed to evaluate the effect of 3-month supplementation of bovine colostrum (BOV-COL; 8x400 mg per day) on the outcomes of depression treatment in hospitalized patients with substance use disorder (SUD). The hypothesis is that BOV-COL supplementation as an add-on treatment results in favorable alternations in selected blood inflammatory markers or neurotransmitters, leading to better depression treatment outcomes compared with placebo (PLA). Methods Patients with a Minnesota Multiphasic Personality Inventory-2 score ≥60 points were enrolled. Twenty-nine participants (n=18 in the BOV-COL group and n=11 in the PLA group) completed the protocol. Results The mean Beck Depression Inventory-II score was significantly reduced after supplementation in both groups. However, the mean 17-point Hamilton Depression Rating Scale score was decreased in the BOV-COL group, but not in the PLA group. In the BOV-COL group, there was a reduction in interleukin (IL)-1, IL-6, IL-10, the IL-6:IL-10 ratio, IL-17, and tumor necrosis factor alpha (TNF-α), while in the PLA group only IL-6 decreased. Favorable alternations in the total count and differentials of white blood cell subsets were more pronounced in the BOV-COL. There were no changes in neurotransmitter concentrations. Conclusions BOV-COL supplementation is a promising add-on therapy in patients with depression and SUD.